Copper-doped mesoporous silica nanospheres, a promising immunomodulatory agent for inducing osteogenesis. (15th January 2016) - Shi, Mengchao; Chen, Zetao; Farnaghi, Saba; Friis, Thor; Mao, Xueli; Xiao, Yin; Wu, Chengtie
Graphical abstract: Cu-MSN nanospheres with beneficial immunomodulation for osteogenesis. Abstract: The application of mesoporous silica nanospheres (MSNs) loaded with drugs/growth factors to induce osteogenic differentiation of stem cells has been trialed by a number of researchers recently. However, limitations such as high cost, complex fabrication and unintended side effects from supraphysiological concentrations of the drugs/growth factors represent major obstacles to any potential clinical application in the near term. In this study we reported an in situ one-pot synthesis strategy of MSNs doped with hypoxia-inducing copper ions and systematically evaluated the nanospheres by in vitro biological assessments. The Cu-containing mesoporous silica nanospheres (Cu-MSNs) had uniform spherical morphology (∼100 nm), ordered mesoporous channels (∼2 nm) and homogeneous Cu distribution. Cu-MSNs demonstrated sustained release of both silicon (Si) and Cu ions and controlled degradability. The Cu-MSNs were phagocytized by immune cells and appeared to modulate a favorable immune environment by initiating proper pro-inflammatory cytokines, inducing osteogenic/angiogenic factors and suppressing osteoclastogenic factors by the immune cells. The immune microenvironment induced by the Cu-MSNs led to robust osteogenic differentiation of bone mesenchymal stem cells (BMSCs) via the activation of Oncostation M (OSM) pathway. These results suggest that the novel Cu-MSNs could be used as an immunomodulatory agent with osteostimulatory capacity for bone regeneration/therapy application. Statement of significance: In order to stimulate both osteogenesis and angiogenesis of stem cells for further bone regeneration, a new kind of hypoxia-inducing copper doped mesoporous silica nanospheres (Cu-MSNs) were prepared via one-pot synthesis. Biological assessments under immune environment which better reflect the in vivo response revealed that the nanospheres possessed osteostimulatory capacity and had potential as immunomodulatory agent for bone regeneration/therapy application. The strategy of introducing controllable amount of therapeutic ions instead of loading expensive drugs/growth factors in mesoporous silica nanosphere provides new options for bioactive nanomaterial functionalization.